2014
DOI: 10.1120/jacmp.v15i6.4890
|View full text |Cite
|
Sign up to set email alerts
|

Clinical radiation therapy measurements with a new commercial synthetic single crystal diamond detector

Abstract: A commercial version of a synthetic single crystal diamond detector (SCDD) in a Schottky diode configuration was recently released as the new type 60019 microDiamond detector (PTW‐Freiburg, Germany). In this study we investigate the dosimetric properties of this detector to independently confirm that findings from the developing group of the SCDDs still hold true for the commercial version of the SCDDs. We further explore if the use of the microDiamond detector can be expanded to high‐energy photon beams of up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 12 publications
8
42
2
6
Order By: Relevance
“…MC calculated beam quality correction factors, which were 1.003, 1.005 and 1.013 for 1.5, 2.5 and 5.5 cm SDD irradiation plans, respectively, also indicate low absorbed‐dose energy dependence of microDiamonds calibrated in 60 Co beam. These findings are also in line with other studies on microDiamond response in high‐energy photon beams which indicate low energy‐dependence of the detector at the tail regions of percentage depth‐dose curves where low‐energy scattered photons are present …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…MC calculated beam quality correction factors, which were 1.003, 1.005 and 1.013 for 1.5, 2.5 and 5.5 cm SDD irradiation plans, respectively, also indicate low absorbed‐dose energy dependence of microDiamonds calibrated in 60 Co beam. These findings are also in line with other studies on microDiamond response in high‐energy photon beams which indicate low energy‐dependence of the detector at the tail regions of percentage depth‐dose curves where low‐energy scattered photons are present …”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the standard deviation of averaged detector readings did not exceed 0.2%, and no drift was observed in detector readings over time in long‐term stability measurements, again indicating no radiation‐induced damage and long‐lasting preirradiation effects during the measurement period. These findings show a major advantage of microDiamonds over natural diamond detectors and are in line with other studies where negligible dose‐rate dependence and deviations in signal stability within ±0.5% were observed for preirradiation doses below 3 Gy . Nevertheless, several authors observed individual behavior among microDiamond detectors and unusually high preirradiation doses of up to 12 Gy …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The microDiamond system was connected to a PTW UNIDOS dosimeter to measure the charge generated by the photon beams. Several studies on the use of this system in therapeutic dosimetry have been reported [17]- [20].…”
Section: Comparison With Microdiamondmentioning
confidence: 99%